Attempts at memory control induce dysfunctional brain activation profiles in Generalized Anxiety Disorder: An exploratory fMRI study. (30th August 2017) - Diwadkar, Vaibhav A.; Re, Marta; Cecchetto, Filippo; Garzitto, Marco; Piccin, Sara; Bonivento, Carolina; Maieron, Marta; D'Agostini, Serena; Balestrieri, Matteo; Brambilla, Paolo
Abstract: Suppression of aversive memories through memory control has historically been proposed as a central psychological defense mechanism. Inability to suppress memories is considered a central psychological trait in several psychiatric disorders, including Generalized Anxiety Disorder (GAD). Yet, few studies have attempted the focused identification of dysfunctional brain activation profiles when patients with Generalized Anxiety Disorders attempt memory control. Using a well-characterized behavioral paradigm we studied brain activation profiles in a group of adult GAD patients and well-matched healthy controls (HC). Participants learned word-association pairs before imaging. During fMRI when presented with one word of the pair, they were instructed to either suppress memory of, or retrieve the paired word. Subsequent behavioral testing indicated both GAD and HC were able to engage in the task, but attempts at memory control (suppression or retrieval) during fMRI revealed vastly different activation profiles. GAD were characterized by substantive hypo-activation signatures during both types of memory control, with effects particularly strong during suppression in brain regions including the dorsal anterior cingulate and the ventral prefrontal cortex. Attempts at memory control in GAD fail to engage brain regions to the same extent HC, providing a putative neuronal signature for a well-established psychological characteristic of the illness. Highlights: GAD and controls were studied with fMRI and a memory control paradigm. GAD had hypo-engagement of cortical regions particularly during memory suppression. Anxiety appears to alter brain activation profiles during memory control.